Let's talk aliens - Stakeholder perceptions of an alien species differ in time and space - Henke, Theresa; Novoa, Ana; Bárðarson, Hlynur; Ólafsdóttir, Guðbjörg Ásta (Pensoft Publishers, 2024)
Humans play an integral role in biological invasions, from aiding introductions of alien species to experiencing their impacts and holding the ability to manage them. The importance of understanding the dynamics of stakeholders' perceptions on alien species is therefore increasingly recognized. In this study, we used anonymous online surveys to contrast recreational anglers' perceptions towards European flounder ( Platichthys flesus , Linnaeus, 1758) in Iceland, where it is classified as a potentially invasive species, to the perceptions prevailing amongst recreational anglers in the species' native range. We furthermore explored potential temporal changes in the perception of Icelandic recreational anglers. Our results indicate that Icelandic recreational anglers have a highly negative perception towards the European flounder, while in its native range, recreational anglers have positive perceptions towards this species. In Iceland, we have furthermore detected a significant change towards less negative perceptions between the surveys administered in October 2019 and March 2023. Finally, we compared the results of the online surveys and novel, conservation culturomics tools to further explore stakeholder perceptions and public interest in Iceland. The comparison highlighted some limitations that should be considered when using culturomics in very small societies or for small languages. For example, the text mining approaches on newspaper articles and social media conservations detected neutral perceptions in the communication to the public and within the targeted stakeholder group via social media in contrary to the perceptions detected in the online surveys. Moreover, we detected short-term peaks in the public's interest in European flounder and potential drivers of those peaks using Wikipedia pageviews but Google Trends provided mixed and unreproducible results. Overall, our study highlights that stakeholders' perceptions towards an alien species as well as the public's interest in it vary over time and ...